B-site titanium-doped perovskite-oxide composite high-temperature thermistor material as well as preparation method and application thereof
By using perovskite-oxide composite high-temperature thermosensitive materials with B-position titanium doped perovskite-oxide composite, the problem of vacancies of anion and cation vacancies caused by Cr ion volatility in existing high-temperature NTC thermistor materials is solved, and the dense sintering of ceramics and the B-value consistency of wide temperature zones is achieved, which is suitable for the manufacturing of medium and high-temperature thermistors.
Patent Information
- Application Number
- CN202411948069.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-18
AI Technical Summary
In existing high-temperature NTC thermistor materials, Cr ions evaporate at high temperatures, resulting in diffusion and conduction of anion and cation vacancies, increase the B value of the thermal constant of the material, and it is difficult for ceramics to sinter and densely.
The perovskite-oxide composite high-temperature thermal-sensitive material is a composite structure of hexagonal crystal wurtzite structure Y2O3 and the perovskite structure YTi0.5Mn0.5O3 through solid phase method, and the ball milling, calcining, grinding and grinding are carried out, and cold isostatic pressure and high-temperature sintering is finally coated with silver paste on both sides for electrode sintering.
The density of the ceramic is improved, the valence state of the B-position Mn ions is regulated, the vacancies of the anion and cations are reduced, and the B value consistency in the wide temperature zone is improved. The material has obvious negative temperature coefficient characteristics in the range of 25℃-1000℃, and the electrical performance is stable. It is suitable for the manufacture of medium and high-temperature thermistors.
Smart Images

Figure BDA0005214188880000091 
Figure BDA0005214188880000092 
Figure BDA0005214188880000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermistor materials, and in particular to a B-site titanium-doped perovskite-oxide composite high-temperature thermistor material and a preparation method and application thereof. Background Art
[0002] Negative temperature coefficient (NTC) thermistors can be divided into low temperature (<-60℃), medium temperature (-60℃-300℃) and high temperature (>300℃) thermistors according to the operating temperature range. The medium temperature NTC with spinel structure is mainly used in the market. The spinel structure is unstable. At high temperature, ions at the A and B positions will be rearranged, causing the thermistor performance to drift. The perovskite structure is more stable at high temperatures, so it is widely used in the field of high temperature NTC; researchers have developed Y 2 O 3 -YCr 0.5 Mn 0.5 O 3 The high-temperature NTC thermistor of the system has NTC performance up to 1000°C, but the Cr ions in the system will volatilize during high-temperature sintering, polluting the environment while forming anion and cation vacancies. The vacancies diffuse and conduct electricity at high temperatures, increasing the thermal constant B value of the material, and at the same time, the ceramic is difficult to sinter densely. Summary of the invention
[0003] In view of the above-mentioned shortcomings of the prior art, the object of the present invention is to provide a B-site titanium-doped perovskite-oxide composite high-temperature thermistor material and a preparation method and application thereof, so as to solve the problems in the prior art.
[0004] The technical solution of the present invention is:
[0005] On the one hand, the present invention provides a B-site titanium-doped perovskite-oxide composite high-temperature thermistor material, wherein the structure of the material is a hexagonal wurtzite structure Y 2 O 3 Perovskite structure YTi 0.5 Mn 0.5 O 3 Composite structure, the chemical formula of the material is xY 2 O 3 -(1-x)YTi 0.5 Mn 0.5 O 3 , where 0.3≤x≤0.6.
[0006] The second aspect of the present invention provides a method for preparing a B-site titanium-doped perovskite-oxide composite high-temperature thermistor material, characterized in that the preparation method comprises the following steps:
[0007] 1) mixing yttrium trioxide, manganese dioxide and titanium oxide, ball milling them once, drying them, grinding them once and sieving them to obtain a first powder;
[0008] 2) calcining the first powder obtained in step 1), ball milling it for a second time, drying it, grinding it for a second time and sieving it to obtain a second powder;
[0009] 3) adding the second powder obtained in step 2) into the PVA aqueous solution, grinding and drying, grinding three times and sieving to obtain a third powder;
[0010] 4) forming the third powder obtained in step 3) into a block, performing cold isostatic pressing, and sintering to obtain a perovskite-oxide composite high-temperature negative temperature coefficient thermistor ceramic material;
[0011] 5) The perovskite-oxide composite high-temperature negative temperature coefficient thermistor ceramic material of step 4) is uniformly coated with silver paste on both sides, dried, and electrode sintered to obtain a B-site titanium-doped perovskite-oxide composite high-temperature thermistor material.
[0012] The third aspect of the present invention provides the use of the B-site titanium-doped perovskite-oxide composite high-temperature thermistor material of the present invention and / or the B-site titanium-doped perovskite-oxide composite high-temperature thermistor material prepared by the preparation method of the present invention in a high-temperature thermistor.
[0013] By adopting the above technical solution, the beneficial effects of the present invention are:
[0014] The present invention discloses a B-site titanium-doped perovskite-oxide composite high-temperature thermosensitive material and a preparation method thereof. The solid phase method is used to mix yttrium, manganese and titanium oxides for ball milling, calcination, secondary ball milling and grinding granulation to obtain a negative temperature coefficient thermistor powder material. The powder material is then pressed into a block and then cold isostatically pressed. After high-temperature sintering, high-temperature silver paste electrodes are coated on both sides to obtain a thermistor disc. The disc thermistor is a composite xY 2 O 3 -(1-x)YTi 0.5 Mn 0.5 O 3 (0.3≤x≤0.6) Ceramic material, xY 2 O 3 -(1-x)YTi 0.5 Mn 0.5 O 3 (0.3≤x≤0.6) Material constant is B 25℃ / 1000℃ =3541K-3598K, the resistivity is 1.37×10 at 25℃ 5 Ω·cm-1.48×10 7The composite high-temperature thermistor material prepared by the method of the present invention has stable performance. The thermistor material has an obvious negative temperature coefficient characteristic in the temperature range of 25°C-1000°C. The linearity of the lnρ-1 / T relationship of the material's resistance-temperature characteristic is good. The B value and ρ value of the material are adjustable. It is suitable for manufacturing high-temperature thermistors. The comparison sample 0.6Y 2 O 3 -0.4YCr 0.5 Mn 0.5 O 3 The performance of the material constant is B 25 / 500 =3799K, B 500 / 1000 =5888K, 25℃ resistivity is 3.27×10 5 Ω·cm. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 is xY in the embodiment of the present invention 2 O 3 -(1-x)YTi 0.5 Mn 0.5 O 3 (0.3≤x≤0.6) and Comparative Example 0.6Y 2 O 3 -0.4YCr 0.5 Mn 0.5 O 3 RT resistance-temperature characteristic curve of thermistor ceramic material.
[0016] Figure 2 is xY in the embodiment of the present invention 2 O 3 -(1-x)YTi 0.5 Mn 0.5 O 3 (0.3≤x≤0.6) and Comparative Example 0.6Y 2 O 3 -0.4YCr 0.5 Mn 0.5 O 3 Resistance-temperature characteristic curve of thermistor ceramic material LnR-1000 / T.
[0017] Figure 3 For example xY of the present invention 2 O 3 -(1-x)YTi 0.5 Mn 0.5 O 3 (0.3≤x≤0.6) and Comparative Example 0.6Y 2 O 3 -0.4YCr 0.5 Mn 0.5 O 3X-ray diffraction pattern of thermosensitive ceramic materials.
[0018] Figure 4 is xY in the embodiment of the present invention 2 O 3 -(1-x)YTi 0.5 Mn 0.5 O 3 (0.3≤x≤0.6) and Comparative Example 0.6Y 2 O 3 -0.4YCr 0.5 Mn 0.5 O 3 SEM image of thermosensitive ceramic material, (a) is 0.6Y 2 O 3 -0.4YCr 0.5 Mn 0.5 O 3 SEM images of thermosensitive ceramic materials, (b)-(f) are 0.6Y 2 O 3 -0.4YTi 0.5 Mn 0.5 O 3 SEM images and energy spectrum of thermosensitive ceramic materials. DETAILED DESCRIPTION
[0019] Hereinafter, a B-site titanium-doped perovskite-oxide composite high-temperature thermosensitive material, a preparation method thereof, and an application embodiment of the present invention are described in detail.
[0020] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0021] Existing Y 2 O 3 -YCr 0.5 Mn 0.5 O 3 The system thermistor generates vacancies due to the volatilization of Cr at high temperature, which makes it difficult for the ceramic to be sintered densely, and at the same time leads to an increase in the thermal constant B value in the high temperature section. 2 O 3 Phase and Ti doping to regulate the electrical properties of thermosensitive ceramic materials, Ti 4+ Doping improves the density of ceramic sintering, and at the same time regulates the valence state of Mn ions at the B position, reduces anion and cation vacancies, and improves the consistency of B value in a wide temperature range. The thermistor material prepared by the present invention has obvious negative temperature resistance coefficient characteristics in the temperature range of 25°C-1000°C, the material system has stable electrical properties, the lnρ-1 / T curve of the material resistance-temperature characteristic has good linearity, the B value and ρ value are adjustable, and it is suitable for manufacturing thermistors used in medium and high temperatures. On this basis, this application is completed.
[0022]
B-site titanium-doped perovskite-oxide composite high-temperature thermistor material
[0023] The present invention provides a B-site titanium-doped perovskite-oxide composite high-temperature thermistor material, wherein the structure of the material is a hexagonal wurtzite structure high-resistance phase Y 2 O 3 Perovskite low-resistance phase YTi 0.5 Mn 0.5 O 3 Composite structure. The chemical formula of the material is xY 2 O 3 -(1-x)YTi 0.5 Mn 0.5 O 3 , where 0.3≤x≤0.6.
[0024] In some embodiments, 0.3≤x≤0.4, 0.4≤x≤0.6, 0.4≤x≤0.5 or 0.5≤x≤0.6.
[0025] The measurement temperature range of the B-site titanium-doped perovskite-oxide composite high-temperature thermistor material is 25°C-1000°C, and the material constant is B 25 / 1000 =3541-3598K, resistivity at 25℃ is 1.37×10 5 -1.48×10 7 Ω·cm.
[0026]
Preparation method of B-site titanium-doped perovskite-oxide composite high-temperature thermistor material
[0027] The present invention also provides a method for preparing a B-site titanium-doped perovskite-oxide composite high-temperature thermistor material, the preparation method comprising the following steps:
[0028] 1) mixing yttrium trioxide, manganese dioxide and titanium oxide, ball milling them once, drying them, grinding them once and sieving them to obtain a first powder;
[0029] 2) calcining the first powder obtained in step 1), ball milling it for a second time, drying it, grinding it for a second time and sieving it to obtain a second powder;
[0030] 3) adding the second powder obtained in step 2) into the PVA aqueous solution, grinding and drying, grinding three times and sieving to obtain a third powder;
[0031] 4) forming the third powder obtained in step 3) into a block, performing cold isostatic pressing, and sintering to obtain a perovskite-oxide composite high-temperature negative temperature coefficient thermistor ceramic material;
[0032] 5) The perovskite-oxide composite high-temperature negative temperature coefficient thermistor ceramic material of step 4) is uniformly coated with silver paste on both sides, dried, and electrode sintered to obtain a B-site titanium-doped perovskite-oxide composite high-temperature thermistor material.
[0033] In the preparation method provided by the present invention, step 1) is to mix yttrium trioxide, manganese dioxide and titanium oxide, perform ball milling once, dry and grind once, and sieve to obtain the first powder. Specifically:
[0034] In step 1) of the present invention, the first ball milling is horizontal ball milling. Specifically, the mixed raw materials and zirconium oxide ball milling beads are placed in a polyethylene ball milling tank and horizontally ball milled with alcohol as a medium. The alcohol can be, for example, anhydrous ethanol.
[0035] In step 1) of the present invention, the horizontal ball milling time is 6 to 48 hours, which can be 6 to 24 hours or 24 to 48 hours.
[0036] In step 1) of the present invention, the first grinding is carried out in an agate mortar.
[0037] In step 1) of the present invention, in one specific embodiment, according to xY 2 O 3 -(1-x)YTi 0.5 Mn 0.5 O 3 (0.3≤x≤0.6), yttrium trioxide, manganese dioxide, and titanium oxide are weighed separately and mixed, the mixed raw materials and zirconium oxide ball milling beads are put into a polyethylene ball mill, and horizontal ball milling is carried out for 2 hours with anhydrous ethanol as a medium. After drying, the mixture is placed in an agate mortar and ground and sieved once to obtain a powder.
[0038] In the preparation method provided by the present invention, step 2) is to calcine the first powder obtained in step 1), ball-mill it for a second time, dry it, grind it for a second time and sieve it to obtain the second powder. Specifically:
[0039] In step 2) of the present invention, the temperature of calcining the first powder is 950-1250°C, which can be 950-1150°C, 1150-1250°C, etc. The calcining time of the first powder is 2-6 hours, which can be 2-4 hours or 4-6 hours.
[0040] In step 2) of the present invention, the first powder after calcination is subjected to secondary ball milling after preliminary grinding. The secondary ball milling is a horizontal ball milling. The time of the secondary ball milling is 6 to 48 hours, which can be 6 to 24 hours or 24 to 48 hours.
[0041] In step 2) of the present invention, the secondary grinding is carried out in an agate mortar.
[0042] In step 2) of the present invention, in a specific embodiment, the powder obtained in step 1) is calcined at 950-1250° C. for 2 hours, initially ground in an agate mortar and then horizontally ball milled for 2 hours, dried, placed in an agate mortar and ground again and sieved to obtain the powder.
[0043] In the preparation method provided by the present invention, step 3) is to add the second powder obtained in step 2) into the PVA aqueous solution, grind it evenly and then dry it, grind it three times and sieve it to obtain the third powder. Specifically:
[0044] In step 3) of the present invention, the mass fraction of the PVA aqueous solution (polyvinyl alcohol aqueous solution) is 4% to 8%, which can be 4% to 5% or 5% to 8%. The PVA aqueous solution is 10% to 20% of the mass of the second powder, which can be 10% to 15%, 15% to 20%, etc.
[0045] In step 3) of the present invention, in a specific embodiment, 10%-20% by mass of the second powder and 5% by mass of PVA aqueous solution are added to the second powder obtained in step 2), and the mixture is ground in an agate mortar and then dried, and then ground again and sieved to obtain a powder.
[0046] In the preparation method provided by the present invention, step 4) is to form the third powder block obtained in step 3) and perform cold isostatic pressing, and sintering to obtain the perovskite-oxide composite high-temperature negative temperature coefficient thermistor ceramic material. Specifically:
[0047] In step 4) of the present invention, the briquetting is first pre-pressed into a disc, and then pressure is maintained. For example, the pressure of the briquetting is 100-300MPa, which can be 100-200MPa or 200-300MPa. The diameter of the disc is Φ8mm-Φ20mm, which can be Φ8mm-Φ12mm or Φ12mm-Φ20mm. The thickness is 0.5-1.3mm, which can be 0.5-1.0mm or 1.0-1.3mm. The pressure holding time is 3-5 minutes.
[0048] In step 4) of the present invention, the cold isostatic pressing is carried out at a pressure of 200-300 MPa for 3-5 minutes.
[0049] In step 4) of the present invention, the sintering temperature is 1420°C-1500°C, and can be 1420°C-1460°C or 1460°C-1500°C.
[0050] In step 4) of the present invention, in a specific embodiment, the third powder obtained in step 3) is pre-pressed into a Φ12mm, 1mm thick disc at a pressure of 200MPa, and the holding time is 3-5 minutes. The formed block material is cold isostatically pressed at a pressure of 200-300MPa for 3-5 minutes, and then sintered at 1420℃-1500℃ for 5 hours to obtain a perovskite-oxide composite high-temperature negative temperature coefficient thermistor ceramic material.
[0051] In the preparation method provided by the present invention, step 5) is to evenly coat the front and back sides of the perovskite-oxide composite high-temperature negative temperature coefficient thermistor ceramic material of step 4) with silver paste, dry it, and perform electrode sintering to obtain a B-site titanium-doped perovskite-oxide composite high-temperature thermistor material.
[0052] In step 5) of the present invention, the temperature of the silver paste is 500-700°C, and can be 500-600°C or 600-700°C.
[0053] In step 5) of the present invention, the electrode is sintered at a heating rate of 8 to 10° C. per minute, at 450 to 550° C. for 4 to 10 minutes, and at 750 to 800° C. for 8 to 15 minutes.
[0054] In step 5) of the present invention, in a specific embodiment, the ceramic material sintered in step 4) is evenly coated with high-temperature silver paste on both sides and dried at 120°C, and then the electrode is sintered at a heating rate of 10°C per minute, 500°C for 4 minutes, and 800°C for 10 minutes, so that the measurement temperature range is 25°C-1000°C, and the material constant is B 25 / 1000 =3541-3598K, resistivity at 25℃ is 1.37×10 5 -1.48×10 7Ω·cm perovskite-oxide composite high-temperature thermistor material.
[0055]
use
[0056] The present invention also provides the use of the B-site titanium-doped perovskite-oxide composite high-temperature thermistor material as described in the first aspect of the present invention and / or the B-site titanium-doped perovskite-oxide composite high-temperature thermistor material prepared by the preparation method as described in the second aspect of the present invention in a high-temperature thermistor.
[0057] The beneficial effects of the present invention are further illustrated below in conjunction with embodiments.
[0058] In order to make the invention purpose, technical scheme and beneficial technical effect of the present invention clearer, the present invention is further described in detail below in conjunction with examples. However, it should be understood that the examples of the present invention are only for explaining the present invention, not for limiting the present invention, and the examples of the present invention are not limited to the examples given in the specification. The specific experimental conditions or operating conditions not specified in the examples are made under conventional conditions, or are made under the conditions recommended by the material supplier.
[0059] In addition, it should be understood that one or more method steps mentioned in the present invention do not exclude the existence of other method steps before or after the combination step or the insertion of other method steps between these explicitly mentioned steps, unless otherwise specified; it should also be understood that the combination connection relationship between one or more devices / apparatuses mentioned in the present invention does not exclude the existence of other devices / apparatuses before or after the combination device / apparatus or the insertion of other devices / apparatuses between these explicitly mentioned two devices / apparatuses, unless otherwise specified. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.
[0060] In the following examples, unless otherwise specified, various raw materials of the present invention can be purchased from the market or prepared according to conventional methods in the art.
[0061] Example 1
[0062] a. Press 0.6Y 2 O 3 -0.4YTi 0.5 Mn 0.5 O 3The composition of the present invention is as follows: 361 g of yttrium trioxide, 17.4 g of manganese dioxide and 16 g of titanium oxide are weighed and mixed respectively; the mixed raw materials and 300 zirconium oxide ball milling beads with a diameter of 6 mm are placed in a polyethylene ball milling jar; 500 g of anhydrous ethanol is used as a medium for horizontal ball milling for 2 hours; after drying, the mixture is placed in an agate mortar and ground and sieved to obtain a powder;
[0063] b. calcining the powder obtained in step a at 1050° C. for 2 hours, grinding it in an agate mortar and then horizontally ball milling it for 2 hours, drying it, grinding it in an agate mortar and sieving it to obtain a powder;
[0064] c. Add 10% by weight of the powder and 5% by weight of a PVA aqueous solution to the powder obtained in step b, grind evenly in an agate mortar and dry, grind again and sieve to obtain a powder;
[0065] d. The powder obtained in step c is pre-pressed into a Φ12 mm, 1 mm thick disc at a pressure of 200 MPa for 5 minutes, and the formed block material is cold isostatically pressed at a pressure of 200-300 MPa for 5 minutes, and then sintered at 1500° C. for 5 hours to obtain a perovskite-oxide composite high-temperature negative temperature coefficient thermistor ceramic material;
[0066] e. The ceramic material sintered in step d is evenly coated with high-temperature silver paste on both sides and dried at 120°C. Then, the electrode is sintered at a heating rate of 10°C per minute, 500°C for 4 minutes, and 800°C for 10 minutes. The measurement temperature range is 25°C-1000°C, and the material constant is B. 25 / 1000 =3541K, 25℃ resistivity is 1.48×10 7 Ω·cm perovskite-oxide composite high-temperature thermistor material. After Ti replaces Cr at the B position, the density of the ceramic is improved and the consistency of the B value is improved.
[0067] Among them, the RT resistance-temperature characteristic curve of the thermistor ceramic material of Example 1 is shown in Figure 1 The temperature resistance characteristic curve of the thermal-sensitive ceramic material LnR-1000 / T of Example 1 is shown in Figure 2 The X-ray diffraction pattern of the thermosensitive ceramic material of Example 1 is shown in Figure 3 The SEM image and energy spectrum of the thermosensitive ceramic material of Example 1 are shown in Figure 4 b~4f.
[0068] Example 2
[0069] a. Press 0.5Y 2 O 3 -0.5YTi 0.5 Mn 0.5 O 3The composition of the present invention is as follows: 338.7 g of yttrium trioxide, 21.7 g of manganese dioxide and 20 g of titanium oxide are weighed and mixed respectively; the mixed raw materials and 300 zirconium oxide ball milling beads with a diameter of 6 mm are put into a polyethylene ball milling jar; 500 g of anhydrous ethanol is used as a medium for horizontal ball milling for 2 hours; after drying, the mixture is placed in an agate mortar and ground and sieved to obtain a powder;
[0070] b. calcining the powder obtained in step a at 1050° C. for 2 hours, grinding it in an agate mortar and then horizontally ball milling it for 2 hours, drying it, grinding it in an agate mortar and sieving it to obtain a powder;
[0071] c. Add 10% by weight of the powder and 5% by weight of a PVA aqueous solution to the powder obtained in step b, grind evenly in an agate mortar and dry, grind again and sieve to obtain a powder;
[0072] d. The powder obtained in step c is pre-pressed into a Φ12 mm, 1 mm thick disc at a pressure of 200 MPa for 5 minutes, and the formed block material is cold isostatically pressed at a pressure of 200 MPa for 5 minutes, and then sintered at 1480° C. for 5 hours to obtain a perovskite-oxide composite high-temperature negative temperature coefficient thermistor ceramic material;
[0073] e. The ceramic material sintered in step d is evenly coated with high-temperature silver paste on both sides and dried at 120°C. Then, the electrode is sintered at a heating rate of 10°C per minute, 500°C for 4 minutes, and 800°C for 10 minutes. The measurement temperature range is 25°C-1000°C, and the material constant is B. 25 / 1000 =3598K, 25℃ resistivity is 2.92×10 5 Ω·cm perovskite-oxide composite high-temperature thermistor material.
[0074] Among them, the RT resistance-temperature characteristic curve of the thermistor ceramic material of Example 2 is shown in Figure 1 The temperature resistance characteristic curve of the thermal-sensitive ceramic material LnR-1000 / T of Example 2 is shown in Figure 2 The X-ray diffraction pattern of the thermosensitive ceramic material of Example 2 is shown in Figure 3 .
[0075] Example 3
[0076] a. Press 0.4Y 2 O 3 -0.6YTi 0.5 Mn 0.5 O 3The composition of the present invention is as follows: 316 g of yttrium trioxide, 26.1 g of manganese dioxide and 24 g of titanium oxide are weighed and mixed respectively; the mixed raw materials and 300 zirconium oxide ball milling beads with a diameter of 6 mm are placed in a polyethylene ball milling jar; 500 g of anhydrous ethanol is used as a medium for horizontal ball milling for 2 hours; after drying, the mixture is placed in an agate mortar and ground and sieved to obtain a powder;
[0077] b. calcining the powder obtained in step a at 1050° C. for 2 hours, grinding it in an agate mortar and then horizontally ball milling it for 2 hours, drying it, grinding it in an agate mortar and sieving it to obtain a powder;
[0078] c. Add 10% by weight of the powder and 5% by weight of a PVA aqueous solution to the powder obtained in step b, grind evenly in an agate mortar and dry, grind again and sieve to obtain a powder;
[0079] d. The powder obtained in step c is pre-pressed into a Φ12 mm, 1 mm thick disc at a pressure of 200 MPa for 5 minutes, and the formed block material is cold isostatically pressed at a pressure of 200 MPa for 5 minutes, and then sintered at 1450° C. for 5 hours to obtain a perovskite-oxide composite high-temperature negative temperature coefficient thermistor ceramic material;
[0080] e. The ceramic material sintered in step d is evenly coated with high-temperature silver paste on both sides and dried at 120°C. Then, the electrode is sintered at a heating rate of 10°C per minute, 500°C for 4 minutes, and 800°C for 10 minutes. The measurement temperature range is 25°C-1000°C, and the material constant is B. 25 / 1000 =3566K, 25℃ resistivity is 1.37×10 5 Ω·cm perovskite-oxide composite high-temperature thermistor material.
[0081] Among them, the RT resistance-temperature characteristic curve of the thermistor ceramic material of Example 3 is shown in Figure 1 The temperature resistance characteristic curve of the thermal-sensitive ceramic material LnR-1000 / T of Example 3 is shown in Figure 2 The X-ray diffraction pattern of the thermosensitive ceramic material of Example 3 is shown in Figure 3 .
[0082] Comparative Example 1
[0083] a. Press 0.6Y 2 O 3 -0.4YCr 0.5 Mn 0.5 O 3The composition of the present invention is as follows: 361 g of yttrium trioxide, 17.4 g of manganese dioxide and 30.4 g of chromium trioxide are weighed and mixed respectively; the mixed raw materials and 300 zirconium oxide ball milling beads with a diameter of 6 mm are placed in a polyethylene ball milling jar, and horizontal ball milling is performed for 2 hours with 500 g of anhydrous ethanol as a medium; after drying, the mixture is placed in an agate mortar and ground and sieved to obtain a powder;
[0084] b. calcining the powder obtained in step a at 1050° C. for 2 hours, grinding it in an agate mortar and then horizontally ball milling it for 2 hours, drying it, grinding it in an agate mortar and sieving it to obtain a powder;
[0085] c. Add 10% by weight of the powder and 5% by weight of a PVA aqueous solution to the powder obtained in step b, grind evenly in an agate mortar and dry, grind again and sieve to obtain a powder;
[0086] d. The powder obtained in step c is pre-pressed into a Φ12 mm, 1 mm thick disc at a pressure of 200 MPa for 5 minutes, and the formed block material is cold isostatically pressed at a pressure of 200 MPa for 5 minutes, and then sintered at 1470° C. for 5 hours to obtain a perovskite-oxide composite high-temperature negative temperature coefficient thermistor ceramic material;
[0087] e. The ceramic material sintered in step d is evenly coated with high-temperature silver paste on both sides and dried at 120°C. Then, the electrode is sintered at a heating rate of 10°C per minute, 500°C for 4 minutes, and 800°C for 10 minutes. The measurement temperature range is 25°C-1000°C, and the material constant is B. 25 / 500 =3799K, B 500 / 1000 =5888K, 25℃ resistivity is 3.27×10 5 Ω·cm perovskite-oxide composite high-temperature thermistor material.
[0088] Among them, the RT resistance temperature characteristic curve of the thermistor ceramic material of comparative example 1 is shown in Figure 1 The temperature resistance characteristic curve of the thermal ceramic material LnR-1000 / T of comparative example 1 is shown in Figure 2 The X-ray diffraction pattern of the thermosensitive ceramic material of Comparative Example 1 is shown in Figure 3 The SEM image of the thermosensitive ceramic material of Comparative Example 1 is shown in Figure 4 a.
[0089] Table 1. Performance parameters of thermistor materials in the examples and comparative examples
[0090]
[0091] Table 2 Performance parameters of comparative thermistor materials
[0092]
[0093]
[0094] Note: 1)ρ 25 (Ω·cm) indicates the resistivity at room temperature
[0095] 3) B 25 / 1000 Indicates the B value constant at room temperature and 1000℃
[0096] 4) B 25 / 500 Indicates the B value constant at room temperature and 500°C
[0097] 5) B 500 / 1000 Indicates the B value constant at 500℃ and 1000℃
[0098] 6) R 2 The linearity of the lnρ-1 / T relationship curve (R 2 The closer the value is to 1, the better the linearity)
[0099] In summary, the present invention effectively overcomes various shortcomings of the prior art and has high industrial utilization value.
[0100] The above is only a preferred embodiment of the present invention, and is not any formal or substantial limitation of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the method of the present invention, and these improvements and supplements should also be regarded as the protection scope of the present invention. Any technician familiar with this profession, without departing from the spirit and scope of the present invention, can make some changes, modifications and evolutions of the technical content disclosed above, which are equivalent embodiments of the present invention; at the same time, any changes, modifications and evolutions of any equivalent changes made to the above embodiments based on the essential technology of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A B-site titanium-doped perovskite-oxide composite high-temperature thermistor material, characterized in that: The structure of the material is hexagonal wurtzite structure Y2O3 and perovskite structure YTi 0.5 Mn 0.5 O3 composite structure, the chemical formula of the material is xY2O3-(1-x)YTi 0.5 Mn 0.5 O3, where 0.3≤x≤0.
6.
2. The B-site titanium-doped perovskite-oxide composite high-temperature thermistor material according to claim 1, characterized in that: Also includes any one or more of the following features: A1) 0.4 ≤ x ≤ 0.6; A2) The measurement temperature range of the B-site titanium-doped perovskite-oxide composite high-temperature thermistor material is 25°C-1000°C, and the material constant is B 25 / 1000 =3541-3598K, resistivity at 25℃ is 1.37×10 5 -1.48×10 7 Ω·cm.
3. The method for preparing the B-site titanium-doped perovskite-oxide composite high-temperature thermistor material according to any one of claims 1 to 2, characterized in that: The preparation method comprises the following steps: 1) mixing yttrium trioxide, manganese dioxide and titanium oxide, ball milling them once, drying them, grinding them once and sieving them to obtain a first powder; 2) calcining the first powder obtained in step 1), ball milling it for a second time, drying it, grinding it for a second time and sieving it to obtain a second powder; 3) adding the second powder obtained in step 2) into the PVA aqueous solution, grinding and drying, grinding three times and sieving to obtain a third powder; 4) forming the third powder obtained in step 3) into a block, performing cold isostatic pressing, and sintering to obtain a perovskite-oxide composite high-temperature negative temperature coefficient thermistor ceramic material; 5) The perovskite-oxide composite high-temperature negative temperature coefficient thermistor ceramic material of step 4) is uniformly coated with silver paste on both sides, dried, and electrode sintered to obtain a B-site titanium-doped perovskite-oxide composite high-temperature thermistor material.
4. The method for preparing the B-site titanium-doped perovskite-oxide composite high-temperature thermistor material according to claim 3, characterized in that: Also includes any one or more of the following features: B1) In step 1), the first ball milling is a horizontal ball milling; B2) In step 1), the primary grinding is carried out in an agate mortar.
5. The method for preparing the B-site titanium-doped perovskite-oxide composite high-temperature thermistor material according to claim 4, characterized in that: Also includes any one or more of the following features: B11) In step 1), the mixed raw materials and zirconium oxide ball milling beads are placed in a polyethylene ball milling tank and horizontally ball milled using alcohol as a medium; B12) In step 1), the horizontal ball milling time is 6 to 48 hours.
6. The method for preparing the B-site titanium-doped perovskite-oxide composite high-temperature thermistor material according to claim 3, characterized in that: Also includes any one or more of the following features: C1) In step 2), the first powder is calcined at a temperature of 950-1250°C; C2) In step 2), the first powder is calcined for 2 to 6 hours; C3) in step 2), the calcined first powder is subjected to secondary ball milling after preliminary grinding; C4) In step 2), the secondary grinding is carried out in an agate mortar.
7. The method for preparing the B-site titanium-doped perovskite-oxide composite high-temperature thermistor material according to claim 6, characterized in that: In step 2), any one or more of the following features are also included: C31) in step 2), the secondary ball milling is a horizontal ball milling; C32) In step 2), the secondary ball milling time is 6 to 48 hours.
8. The method for preparing the B-site titanium-doped perovskite-oxide composite high-temperature thermistor material according to claim 3, characterized in that: Also includes any one or more of the following features: D1) In step 3), the mass fraction of the PVA aqueous solution is 4% to 8%; D2) In step 3), the PVA aqueous solution is 10%-20% of the mass of the second powder; D3) In step 4), the briquetting is first pre-pressed into a disc and then maintained under pressure; D4) in step 4), the cold isostatic pressing is carried out at a pressure of 100-300 MPa for 3-5 minutes; D5) In step 4), the sintering temperature is 1420°C-1500°C; D6) In step 4), the sintering time is 3 to 8 hours; D7) In step 5), the temperature of the silver paste is 500-700°C; D8) In step 5), the electrode is sintered at a heating rate of 8-10°C per minute, at 450-550°C for 4-10 minutes, and at 750-800°C for 8-15 minutes.
9. The method for preparing the B-site titanium-doped perovskite-oxide composite high-temperature thermistor material according to claim 3, characterized in that: In step 4), any one or more of the following features are also included: D31) In step 4), the pressure of the briquetting is 100-300 MPa; D32) In step 4), the diameter of the disc is Φ8 mm to Φ20 mm, and the thickness is 0.5 to 1.3 mm; D33) In step 4), the holding time is 3-5 minutes.
10. Use of the B-site titanium-doped perovskite-oxide composite high-temperature thermistor material according to any one of claims 1 to 2 and / or the B-site titanium-doped perovskite-oxide composite high-temperature thermistor material prepared according to the preparation method according to any one of claims 3 to 9 in a high-temperature thermistor.